Adaptive element free Galerkin method for 2D stress analysis - Zhou, Chengen. (2008)
In many applications involving problem domains with complicated geometry, mesh generation could be far more time-consuming and expensive than the assembly and solution of the finite element equations. More importantly, the structured character of Finite Element Method (FEM) limits its application in problems involving moving discontinuities, complex meshes.